Reflections on evaluation of scientific production – a special look at Brazil (Research, Society and Development, 2022)
In this article, we bring some aspects of scientific output evaluation with a look at Brazil. Initially, we present a brief context of scientific production in Brazil and address metrics, such as the impact factor, used to assess the impact of this production on the national and international scientific community and to support decision-making on research funding. Next, we discuss factors that influence the citation of articles and other indicators, which also assess the quality of scientific production. Considering characteristics of the Areas of Knowledge features of scientific journals are punctuated, the Open Access movement points to the need for a public policy to guide the participation of Brazilian research in this new model of making science. Finally, we bring up the issue of the funding needed to encourage scientific production. The objective of reflecting, in this study, on the evaluation of Brazilian scientific output is to raise awareness and mobilize the different actors in the process in favor of a more accessible science that recognizes the specificities of the areas and values their transfer of knowledge, contributing to solving problems of society.